(untitled) (Revista Contexto & Saúde, 2026)
Investigate the use of anxiolytics/antidepressants by graduate students in Brazil during the COVID-19 pandemic. An analytical cross-sectional study was conducted involving 2225 graduate students. For such, three questionnaires were made available on the SurveyMonkey® platform: one addressing sociodemographic characteristics, a questionnaire addressing aspects related to the course and the self-perceived impact of the COVID-19 pandemic on education, and the Brazilian version of the Depression, Anxiety and Stress Scale (DASS-21), which was employed to measure psychological suffering. Data analysis was performed with the aid of the R software, version 4.3.2, and involved Poisson regression analysis with robust variance (α = 5%), with the estimation of prevalence ratios (PR) and respective 95% confidence intervals (CI). The prevalence of anxiolytic/antidepressant use was 24.0%. The use of these medications was significantly associated with age (PR = 1.03; 95% CI: 1.02 - 1.04), a higher psychological suffering score (PR = 1.01; 95% CI: 1.01 - 1.01), being under psychological/psychiatric care (PR = 6.09; 95% CI: 4.58 – 8.10), being unemployed (PR = 1.22; 95% CI: 1.05 - 1.43), residing in the South and Midwest regions of Brazil (PR = 1.29; 95% CI: 1.01 - 1.64) and being a student of the human sciences (PR = 1.26; 95% CI: 1.04 - 1.53). It is concluded that age, psychological suffering, being under psychological/psychiatric care, being unemployed, residing in the South and Midwest regions of Brazil and being a student of the human sciences exerted an influence on the use of anxiolytics/antidepressantsCOVID-19 pandemic.